Political Aspects of the Dispute over the Macedonian Orthodox Church [MOC] [1991–2014] - Paszkiewicz, Jędrzej (Poznańskie Studia Slawistyczne, 2016)
The dispute about the autocephaly of the Macedonian Orthodox Church (MOC), one of the questions within the discourse on the Macedonian national identity since 1967, gained new significance after 1991, as a consequence of the political emancipation of the Republic of Macedonia (RM). This issue is strongly associated with other concerns, such as the country’s internal integration and the struggle to strengthen its sovereignty. In order to support the MOC the authorities attempt to rally the ethnic Macedonians around the idea of national independence and diminish the influences of other Orthodox Churches on the followers of this denomination in RM. Year 2002 saw the failure of the religious consultation and an imminent schism within MOC. It prompted the authorities to act as a guarantor of the undivided jurisdiction of the MOC over the country’s entire territory. This course of action resulted in worsening of the relations with the neighboring Orthodox Christian countries, since the governments cooperate with their respective Churches to contest the independence of MOC. Moreover, since 2002 the issue of MOC’s status is frequently presented within the context of accusations against the RM’s authorities of breaching the civil and religious rights.